Calcium and cholecalciferol supplementation provides no added benefit to nutritional counseling to improve bone mineral density in survivors of childhood acute lymphoblastic leukemia (ALL). Issue 5 (7th January 2014) - Kaste, S.C.; Qi, A.; Smith, K.; Surprise, H.; Lovorn, E.; Boyett, J.; Ferry, R.J.; Relling, M.V.; Shurtleff, S.A.; Pui, C.H.; Carbone, L.; Hudson, M.M.; et al.
Abstract Background We sought to improve lumbar spine bone mineral density (LS‐BMD) in long‐term survivors of childhood acute lymphoblastic leukemia (ALL) using calcium and cholecalciferol supplementation. Procedure This double‐blind, placebo‐controlled trial randomized 275 participants (median age, 17 [9–36.1] years) with age‐ and gender‐specific LS‐BMD Z‐scores <0 to receive nutritional counseling with supplementation of 1, 000 mg/day calcium and 800 International Unit cholecalciferol or placebo for 2 years. The primary outcome was change in LS‐BMD assessed by quantitative computerized tomography (QCT) at 24 months. Linear regression models were employed to identify the baseline risk factors for low LS‐BMD and to compare LS‐BMD outcomes. Results Pre‐randomization LS‐BMD below the mean was associated with male gender (P = 0.0024), White race (P = 0.0003), lower body mass index (P < 0.0001), and cumulative glucocorticoid doses of ≥5, 000 mg (P = 0.0012). One hundred eighty‐eight (68%) participants completed the study; 77% adhered to the intervention. Mean LS‐BMD change did not differ between survivors randomized to supplements (0.33 ± 0.57) or placebo (0.28 ± 0.56). Participants aged 9–13 years and those 22–35 years had the greatest mean increases in LS‐BMD (0.50 ± 0.66 and 0.37 ± 0.23, respectively). Vitamin D insufficiency (serum 25[OH]D <30 ng/ml) found in 296 (75%), was not associated with LS‐BMD outcomes (P = 0.78). Conclusion Cholecalciferol and calcium supplementation provides no added benefit to nutritional counseling for improving LS‐BMD among adolescent and young adult survivors of ALL (93% of whom had LS‐BMD Z‐scores above the mean at study entry). Pediatr Blood Cancer 2014;61:885–893. © 2014 Wiley Periodicals, Inc.